ANALISIS TEORI BELAJAR BEHAVIOURISTIK SEBAGAI UPAYA PENGEMBANGAN KREATIVITAS PESERTA DIDIK PADA ABAD 21 - Khairani, Yenny; Abdul Hakam, Kama; Muhammad Ganeswara, Ganjar (JISPE Journal of Islamic Primary Education, 2021)
The purpose of this study is to analyze behavioristic learning theory as an effort to develop the character of students' creativity. Descriptive qualitative research method. Data collection techniques in this study used observation, interview, and documentation techniques. Data analysis techniques used in this study were source triangulation analysis and technical triangulation. The analysis is in the form of data collection, data reduction, data presentation, and verification or drawing conclusions. The results of the study explain that the behavioristic learning theory on the character of the creativity of students with the formation of a creative behavior. The form of creativity carried out by schools in developing creative character in creative thinking skills (aptitude) with activities such as creative writing in the form of short stories and opinions, the use of PBL and PJBL learning methods. In the aspect of attitude/non-aptitude by way of inspirational stories, changing the layout of the classroom every week, class cooperatives, outbound training, making woven crafts, embroidery crafts, batik dyeing crafts, cooking competitions, outing classes, class meetings, and cultural festivals.